Agronomic efficiency of phosphorus at different base saturation in soybean yield in Cerrado soils (Research, Society and Development, 2020)
This study aimed to evaluate the agronomic efficiency of phosphorus at different soil base saturation in soybean production. Two experiments were conducted (greenhouse and field) in the 2016/2017 growing season in a DBC experimental design, with a factorial arrangement 3 (base saturation) x 4 (phosphorus levels), with four replications. Number of pods per plant (NVP), number of grains per plant (NGP), first pod height (A1V), number of grains per pod (NGV), one thousand grain weight (PMG) and yield (PROD) were evaluated. In the greenhouse experiment, there was a significant difference for the interaction SxP (base saturation x phosphorus levels) for the variables NVP, NGP and yield, and for the field experiment, only the yield was significant. For the base saturation, only the A1V was significant and for the phosphorus, only the NVP had a significant effect. Phosphorus fertilization in Cerrado soils increases soybean yield and has an agronomic efficiency of 14.59 kg in soils with 50% base saturation and 12.87 kg soybean grains per kilogram of phosphorus applied in soils with base saturation at 70%, within high yield standards.